Piezooptics in Non-Uniform Mechanical Fields. - Vlokh, Rostyslav (Cambridge Scholars Publisher, 2022)
The phenomena of parametric optics, which include the piezooptic effect still remain the fundamental basis for the development of various optical instruments. On the other hand, the existing experimental methods for studying the piezooptic properties of crystalline media are quite imperfect and lead to significant errors. These circumstances highlight the importance and relevance of the further development of piezooptics methods.This book will familiarize the reader with the 2D-polarimetric and interferometric methods in the study of the piezooptic effect under the action of inhomogeneous mech.